PENGUATAN ECOLITERACY SANTRI BERBASIS KEARIFAN LOKAL - Royani, Ahmad; Junaidi, Muhammad (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2024)
Ecoliteracy is a skill to produce someone who has the value of being aware of knowledge, skills about the values and norms of environmental maintenance, and habits that prioritize environmental sustainability. Educational institutions such as madrasah are the main means of introducing the basic principles of ekolgi to students. This service activity was carried out at Madrasah Diniyah Al-Ghazalie Kalibaru Banyuwangi. This institution is a suburban institution located at the western end of the city of Banyuwangi. The purpose of mentoring is; (1) designing learning methods to improve students' environmental literacy skills. (2) conducting educational activities and transferring environmental skills to Madin Al-Ghazalie Kalibaru Banyuwangi students. (3) establish environmental literacy cadres in partner institutions. The method of dedication on strengthening student ecoliteracy uses several methods, including; (1) looking for a slick design in learning activities with ecoliteracy character and (2) providing training activities to students and also ustad / ustadah by presenting reliable facilitators in their fields. From the results of the service, it can be concluded that: first, the form of implementation of Islamic boarding school ecological education can be done through indoor and outdoor programs. This activity can be seen that the environmental love curriculum is directed at making teaching modules that emphasize morals to the environment and environmental jurisprudence. Secondly, to achieve ecological education competence, pesantren covers several learning domains in the form of knowledge, attitudes, skills, and participation. Furthermore, to strengthen sustainability, sustainable assistance is needed, so it is important to form environmental literacy cadres. This activity is more directed at environmental love activities. The selection of cadres or ambassadors for students who love the environment is an implication of classroom learning activities that are applied in daily activities both in madrassas and in their respective homes.